Peningkatan Literasi Siswa Melalui Program Pojok Baca Oleh Kampus Mengajar 6 di Berbagai Sekolah Dasar - Marzela Faiza; Maudina Bunga Khairunnisa; Muhammad Abdul Gani; Ririn Farianti; Riska Rahmawati Hasan; Sopiana Handita Putri (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
Developing and increasing literacy is one of the problems currently being faced. The lack of interest in literacy and interest in reading, especially among children, is caused by, among other things, excessive use of gadgets. With this problem, it is feared that there will be more and more children who have low interest in reading. This research aims to determine the increase in student literacy among children, especially elementary school students, through one of the prestigious independent campus learning (MBKM) programs, namely the Teaching Campus. This increase in literacy will be carried out through one of the work programs implemented, namely the reading corner. The method used in this research is descriptive research. The locations of this research are several elementary schools in West Nusa Tenggara province. The samples used were 5th grade elementary school students and students. The final result of this activity is an increase in reading interest and literacy levels among students at the elementary school level through the Reading Corner program.